Question
upstudy study bank question image url

d) \( (3 x-2): 0,15=6: 5 \) e) \( (x+2): \frac{1}{2}=2: 1 \) f) \( (x-1): 4=3: 5 \)

Ask by Hardy Salinas. in Bosnia and Herzegovina
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are: - **d)** \( x \approx 0.727 \) - **e)** \( x = -1 \) - **f)** \( x = 3.4 \)

Solution

Let's solve each of the given proportions for \( x \). --- ### **d) \( \frac{3x - 2}{0.15} = \frac{6}{5} \)** **Step 1:** Set up the equation from the proportion: \[ \frac{3x - 2}{0.15} = \frac{6}{5} \] **Step 2:** Cross-multiply to eliminate the fractions: \[ (3x - 2) \times 5 = 6 \times 0.15 \] \[ 5(3x - 2) = 0.9 \] **Step 3:** Distribute the 5: \[ 15x - 10 = 0.9 \] **Step 4:** Add 10 to both sides: \[ 15x = 10.9 \] **Step 5:** Divide both sides by 15 to solve for \( x \): \[ x = \frac{10.9}{15} = \frac{109}{150} \approx 0.727 \] --- ### **e) \( \frac{x + 2}{\frac{1}{2}} = \frac{2}{1} \)** **Step 1:** Set up the equation from the proportion: \[ \frac{x + 2}{\frac{1}{2}} = 2 \] **Step 2:** Multiply both sides by \( \frac{1}{2} \) to isolate \( x + 2 \): \[ x + 2 = 2 \times \frac{1}{2} \] \[ x + 2 = 1 \] **Step 3:** Subtract 2 from both sides to solve for \( x \): \[ x = 1 - 2 \] \[ x = -1 \] --- ### **f) \( \frac{x - 1}{4} = \frac{3}{5} \)** **Step 1:** Set up the equation from the proportion: \[ \frac{x - 1}{4} = \frac{3}{5} \] **Step 2:** Cross-multiply to eliminate the fractions: \[ 5(x - 1) = 3 \times 4 \] \[ 5x - 5 = 12 \] **Step 3:** Add 5 to both sides: \[ 5x = 17 \] **Step 4:** Divide both sides by 5 to solve for \( x \): \[ x = \frac{17}{5} = 3.4 \] --- ### **Summary of Solutions:** - **d)** \( x = \frac{109}{150} \approx 0.727 \) - **e)** \( x = -1 \) - **f)** \( x = \frac{17}{5} = 3.4 \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To tackle the equation \( (3x-2): 0.15 = 6: 5 \), you can cross-multiply to eliminate the ratio. This means you will have \( 5(3x - 2) = 0.15 \times 6 \). Simplifying that gives you \( 5(3x - 2) = 0.9 \), leading to the solution for \( x \). For the second equation \( (x + 2): \frac{1}{2} = 2: 1 \), again, cross-multiplying is your friend! This results in \( 1(x + 2) = 2 \times \frac{1}{2} \), simplifying leads to \( x + 2 = 1 \), allowing you to find \( x \) easily. Stay tuned for the last one, \( (x - 1): 4 = 3: 5 \)! Following the same cross-multiplication method, you arrive at \( 5(x - 1) = 12 \) (since \( 3 \times 4 = 12 \)). Solve for \( x \) by distributing and isolating to find that sweet solution!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy